A School-Based Suicide Risk Assessment Strategy. (November 2014) - Nolta, Kristie
While school nurses are often uniquely positioned to conduct suicide risk assessments, many school nurses feel poorly equipped to undertake this venture. This article outlines a plan to put a suicide risk assessment strategy in place.